2022
DOI: 10.1155/2022/9584527
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Long-Term Outcomes in Very Young Patients with Myocardial Infarction with Non-Obstructive Coronary Arteries

Abstract: Background. The main cause of acute coronary syndrome (ACS) is coronary artery obstruction due to atherosclerotic plaque growth or thrombus formation secondary to plaque rupture or erosion. However, there is a subgroup of patients with signs and symptoms suggestive of ACS but without relevant coronary artery obstruction on coronary angiography. This population is defined as myocardial infarction with non-obstructive coronary arteries (MINOCA). The present study analyzes the clinical features and outcomes of ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The study also found associations between poor outcomes in the MINOCA population and cocaine use (HR 14.58, 95% CI 3.08-69.02), family history (HR 6.20, 95% CI 1.40-27.43), and depression (HR 5.16, 95% CI 1.06-25.24). However, their study had a different design compared to ours, as it lacked an elderly control group [17]. A subgroup analysis of the Kaplan-Meier survival analysis of the groups.…”
Section: Discussionmentioning
confidence: 86%
“…The study also found associations between poor outcomes in the MINOCA population and cocaine use (HR 14.58, 95% CI 3.08-69.02), family history (HR 6.20, 95% CI 1.40-27.43), and depression (HR 5.16, 95% CI 1.06-25.24). However, their study had a different design compared to ours, as it lacked an elderly control group [17]. A subgroup analysis of the Kaplan-Meier survival analysis of the groups.…”
Section: Discussionmentioning
confidence: 86%
“…References: [14][15][16][17][18][19][20][21][22][24][25][26][27][28] MIOCA: myocardial infarction with obstructive coronary arteries; MINOCA: myocardial infarction with nonobstructive coronary arteries…”
Section: Figure 5: All-cause Mortalitymentioning
confidence: 99%
“…Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a disease characterized by clinical signs of a myocardial infarction with normal or near-normal coronary arteries on angiography (stenosis <50%) [1,2]. The most prevalent cause of acute coronary syndrome (ACS) is atherosclerotic plaque formation caused by erosion.…”
Section: Introductionmentioning
confidence: 99%